Perhitungan Harga Pokok Produksi Metode Full Costing Sebagai Dasar Penentuan Harga Jual pada Rumah Makan Soto Ayam Lamongan Pakde Tari - NurAnzani, Rika; Alkamaliah, Nazma Al; Harini, Jelita; Hanifah, Kholisa; Meo, Klarita (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This research was conducted to examine the calculation of the cost of goods sold (COGS) as a basis for setting selling prices at Pakde Tari’s Lamongan Chicken Soto Restaurant in Depok city using the full costing method.. The research method used is a descriptive quantitative approach with data collection techniques through direct interviews with business owners and observation. The research results show a difference between the calculation of COGS by the restaurant and using the full costing method. Based on the full costing method, the COGS per serving of Lamongan chicken soup is IDR 8,674.67, while the restaurant's internal calculation is IDR 8,054.67. Furthermore, with the application of a 60% markup percentage, the recommended selling price through the cost plus pricing method is IDR 14,000 per serving after rounding. The research conclusion indicates that using full costing can provide a more accurate calculations, making it a suitable basis for determining optimal selling prices for the sustainability of small-scale culinary businesses.